High‐throughput cell quantification assays for use in cell purification development – enabling technologies for cell production. Issue 5 (8th March 2016) - Zimmermann, Sarah; Gretzinger, Sarah; Scheeder, Christian; Schwab, Marie‐Luise; Oelmeier, Stefan A.; Osberghaus, Anna; Gottwald, Eric; Hubbuch, Jürgen
Abstract: High‐throughput screening (HTS) technology is gaining increasing importance in downstream process development of cell‐based products. The development of such HTS‐technologies, however, is highly dependent on the availability of robust, accurate, and sensitive high‐throughput cell quantification methods. In this article, we compare state‐of‐the‐art cell quantification methods with focus on their applicability in HTS‐platforms for downstream processing of cell‐based products. Sensitivity, dynamic range, and precision were evaluated for four methods that differ in their respective mechanism. In addition, we evaluated the performance of these methods over a range of buffer compositions, medium densities, and viscosities, representing conditions found in many downstream processing methods. We found that CellTiter‐Glo™ and flow cytometry are excellent tools for high‐throughput cell quantification. Both methods have broad working ranges (3–4 log) and performed well over a wide range of buffer compositions. In comparison, CyQuant® Direct and CellTracker™ had smaller working ranges and were more sensitive to changes in buffer composition. For fast and sensitive quantification of a single cell type, CellTiter‐Glo™ performed best, while for more complex cell mixtures flow cytometry is the method of choice. Our analysis will facilitate the selection of the most suitable method for a specific application and provides a benchmark for future HTS development in downstream processing of cell‐based products. Abstract : As the development of cell‐based pharmaceuticals is advancing, new scalable downstream processing strategies are required. In this study, several cell quantification methods that differ in their respective mechanism are validated for applicability in high‐throughput screening platforms for downstream process development. Methods differ significantly in sensitivity, range, robustness, and throughput, and the study provides a guideline for selecting the most suitable assay for a specific application.